DEVELOPING ICT MATERIAL TO ENHANCE EFL TEACHERS PERFORMANCE IN ELT CLASSROOM - Siswandi Siswandi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This paper has identified an exciting future in which the nature of English as a subject is radically changed, embracing new literacies as a focus and a means for learning and teaching. It has also discussed the factors that impede progress. However, this does not mean that our training of future teachers should present the role of ICT in the teaching of English as limited to that of enhancement, providing a tool to support traditional approaches to the teaching and learning of English. On the contrary, it is essential that we encourage student, teachers to appreciate the powerful impact of ICT on English as a subject, the diversity of texts, uses of literacy and means to facilitate teaching and learning it provides. It is therefore essential that student teachers are aware of their potential to transform learning in their classrooms. By supporting them in gaining the knowledge, confidence and critical awareness to recognize the potential of ICT, we may enable them to provide a vibrant and dynamic English curriculum and embrace further change in the future.